Outcomes of Intrauterine Device Insertion by Certified Midwives and Obstetric Nurse Practitioners - Thalita Vital Botelho; Ana Luiza Vilela Borges (Revista Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to evaluate the outcomes of Interval Copper Intrauterine Device (IUD) insertion performed by certified midwives and obstetric nurse practitioners at a Peri-Hospital Birth Center. Methods: a cross-sectional study was conducted involving 75 women who underwent IUD insertion between January 2018 and February 2020. Data collection was carried out using medical records and telephone interviews. Results: no instances of uterine perforation were observed. Expulsion rates of the devices were 1.3% within 30 to 45 days of use and 5.3% within the first year of use. The follow-up removal rate was 4.0%. The average pain score reported was 4.2 (SD = 3.3). Among those who continued using the device, 93.1% expressed satisfaction. Conclusions: the findings demonstrate that IUD insertion by certified midwives and obstetric nurse practitioners is a safe procedure, yielding outcomes comparable to those reported in the existing literature.